Chapter 2 Current discussions on plurilingual pedagogy: Language learning implications in the Arabian Peninsula - Jaafarawi, Nadine (Taylor & Francis, 2023)
English Medium Instruction within higher education is in continuous change as it evolves to meet the needs of both faculty and students. In this chapter, the focus is on highlighting the "transformative" aspects of adopting plurilingual and translanguaging pedagogy to improve language learning, especially in countries within the Arabian Peninsula where English is not the first language. The chapter also sheds light on how instructors could be provided with theoretical frameworks that help them cater to the various multilingual backgrounds brought to the learning environment by the students, which, in turn, impact the design and implementation of teaching activities. These activities could involve plurilingual and translanguaging practices, which at times gather negative perceptions. Therefore, this chapter also examines the reasons for acceptance and the tensions faced by educators when transitioning into new pedagogical practices, highlighting the practical implications of plurilingualism and translanguaging to assist English language in education in countries within the Arabian Peninsula. The goal here is to serve the social and educational transformation of current models of bi/multilingual education in these countries.